2021
DOI: 10.3389/fcvm.2021.737551
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram to Predict Left Atrial Thrombus or Spontaneous Echo Contrast in Patients With Non-valvular Atrial Fibrillation

Abstract: Background: The predictive power of the CHADS2 and CHA2DS2-VASc scores for the presence of Left atrial thrombus (LAT)/ spontaneous echo contrast (SEC) in non-valvular atrial fibrillation (NVAF) is modest. The aim of this analysis is to define clinical and ultrasonic variables associated with LAT/SEC and to propose nomograms for individual risk prediction.Methods: Data on 1,813 consecutive NVAF patients who underwent transesophageal echocardiography (TEE) from January 2016 to January 2021 were collected. The un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…Apparently, reduced flow velocity in the left atrial appendage due to an increase in left atrial volume contributes to stasis and clot formation. This is consistent with transesophageal echocardiographic data which suggest that LAE was an independent risk factor for left atrial thrombus or spontaneous echocardiographic contrast and embolic events ( 31 ). Moreover, our study consolidated the relationship between the LAE and ICVE in AMI patients, and LAE may also represent a potential indication either for initiating or monitoring anticoagulant therapy for the prevention of stroke before the onset of AF in patients with AMI ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…Apparently, reduced flow velocity in the left atrial appendage due to an increase in left atrial volume contributes to stasis and clot formation. This is consistent with transesophageal echocardiographic data which suggest that LAE was an independent risk factor for left atrial thrombus or spontaneous echocardiographic contrast and embolic events ( 31 ). Moreover, our study consolidated the relationship between the LAE and ICVE in AMI patients, and LAE may also represent a potential indication either for initiating or monitoring anticoagulant therapy for the prevention of stroke before the onset of AF in patients with AMI ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…7 Transesophageal Echocardiography Evaluation TEE was performed before catheter ablation or direct current cardioversion for all patients as described in a previous study. 19 Prior to the TEE examination, the details of the procedure were explained for every patient, and all patients provided written informed consent. Thrombus was defined as a circumscribed, uniformly echo dense mass distinct from the underlying left atrial endocardium and pectinate muscles detected in more than 1 imaging plane.…”
Section: Dovepressmentioning
confidence: 99%
“…By comparing NVAF patients with and without SEC, previous studies have identified several risk factors for SEC presence, which are capable of reflecting hemodynamic and hematological status correlated with SEC formation, such as HF/decreased LVEF, LA dilation, increased fibrinogen, C-reactive protein, and D-dimer. 10,[29][30][31] Moreover, severe MR was reported to be protective against SEC owing to the increased shear rate within LA. However, it remained unclear if these parameters were suitable to predict severe SEC.…”
Section: La Hemodynamics and Severe Secmentioning
confidence: 99%